Implementation of Online Learning during the Covid 19 Pandemic at SD Muhammadiyah 2 Sidoarjo - Dwi Prasanti; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
This study aims to find out about the learning strategies used at SD Muhammadiyah 2 Sidoarjo during the covid 19 pandemic. In this research data retrieval by using interviews, documentation and observation. The results obtained in this study are: 1) The way the teacher motivates students to keep the spirit of learning in online learning, 2) The teacher's strategies used in online learning, 3) the perceived obstacles during online learning. This research uses descriptive qualitative method. During the pandemic, SD Muhammadiyah 2 Sidoarjo continued to do learning via zoom and the web. Although learning is now done virtually or online, it is not the same as when implementing direct learning, there are many obstacles faced and obtained by students and teaching staff.